2018
DOI: 10.1111/cid.12614
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the match between cone beam computed tomography and model scan data in template‐guided implant planning: A prospective controlled clinical study

Abstract: In the presence of a sufficient number of residual teeth, the manual matching of model scan data with CBCT data is sufficiently accurate for implant planning and template-guided implementation. The results of the present study suggest that X-ray templates can be dispensed with saving the patient a substantial amount of time and money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
2
31
1
1
Order By: Relevance
“…Previous studies on the accuracy of image matching between optical scans of dental models and CBCT data have reported an error ranging from 0.2 to 0.6 mm 5,14,15 . Comparable to previous trials, the registration errors in this study ranged from 0.27 to 0.52 mm, and the smallest errors were in the group that used the entire image of full‐arch tissue replica for image matching.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies on the accuracy of image matching between optical scans of dental models and CBCT data have reported an error ranging from 0.2 to 0.6 mm 5,14,15 . Comparable to previous trials, the registration errors in this study ranged from 0.27 to 0.52 mm, and the smallest errors were in the group that used the entire image of full‐arch tissue replica for image matching.…”
Section: Discussioncontrasting
confidence: 51%
“…Schnutenhaus et al [38] investigated the clinical accuracy of the CBCT matching method. They concluded that matching CBCT data with model scan data was accurate enough for planning sGIS and suggested that the radiographic template could be dispensed with to save time and money of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of this fully digital planning workflow is that, currently, it can only be adopted in dentate patients. For the surface registration protocol, more than five remaining teeth were necessary to achieve appropriate matching of the CBCT and intraoral scans [8,38]. In addition, the distribution of the remaining teeth is also important.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray data for 3D virtual planning purposes are produced by CBCT and saved as voxel based volumetric DICOM files, whereas the intraoral scans and the wax up/set up of the final restoration are saved as surface polygons in STL format. According to the results of a prospective controlled clinical investigation by Schnutenhaus et al manual alignment between CBCT and model scan data performed using afore mentioned software can lead to mean deviations of 0.2 mm [34]. However, matching CBCT and surface scans and 3D printing surgical guides using SMOP lead to a more accurate implant positioning compared to surgical guides which use physical positioners to transfer the coordinates of the planned drilling slots [35].…”
Section: Discussionmentioning
confidence: 99%